2014
DOI: 10.1371/journal.pone.0099855
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ketamine on Learning and Memory Function, Neuronal Apoptosis and Its Potential Association with miR-214 and PTEN in Adolescent Rats

Abstract: Ketamine, an N-methyl-D-aspartate (NMDA) receptor antagonist, is used as a general pediatric anesthetic and anti-depressive drug. Recent studies suggest that ketamine enhances neuronal apoptosis in developing rats. The goal of this study is to explore whether ketamine could result in learning and memory impairment and neurodegeneration in adolescent rats, and if so, whether the effects of ketamine are associated with miR-214 and PTEN expression. Fifty-day-old SD rats were randomly divided into three groups rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 36 publications
4
31
0
Order By: Relevance
“…Consistent with the above findings, isoflurane and sevoflurane exposure at PD7 and PD14 (but not at PD60) were shown to be associated with decreases in the hippocampal stem cell pool and a reduced number of dentate gyrus granule neurons (28,29). In particular, exposure of adolescent rats (PD50) to ketamine lead to apoptosis only in case of high-dose regimen administration of 80 mgÁkg À1 for 7 days (30). Likewise exposure at PD7 to propofol anesthesia was associated with reduced levels of excitatory neurotransmitters in both the cortex and the hippocampus (31), with increased caspase-3 levels in the hippocampal CA1 region suggesting that these changes were the result of apoptosis (31).…”
Section: Studies Included In Thesupporting
confidence: 74%
“…Consistent with the above findings, isoflurane and sevoflurane exposure at PD7 and PD14 (but not at PD60) were shown to be associated with decreases in the hippocampal stem cell pool and a reduced number of dentate gyrus granule neurons (28,29). In particular, exposure of adolescent rats (PD50) to ketamine lead to apoptosis only in case of high-dose regimen administration of 80 mgÁkg À1 for 7 days (30). Likewise exposure at PD7 to propofol anesthesia was associated with reduced levels of excitatory neurotransmitters in both the cortex and the hippocampus (31), with increased caspase-3 levels in the hippocampal CA1 region suggesting that these changes were the result of apoptosis (31).…”
Section: Studies Included In Thesupporting
confidence: 74%
“…miR‐21 has been identified as an antiapoptotic LH‐induced factor in preovulatory GCs, and it ensures both the survival and differentiation of these cells (Carletti et al., ). The role of miR‐214 in the regulation of cell apoptosis and gonad steroidogenesis (such as progesterone) has been reported previously (Tian, Zeng, Li, Wu, & Wang, ; Wang et al., ). Here, we showed that the miR‐21 expression level increased at the same time as the LH concentration increases before, during, and 3–4 days after ovulation.…”
Section: Discussionsupporting
confidence: 53%
“…However, according to another study, mice exposed to the same dosing paradigm showed no deficits in learning and memory15. We hypothesized that adult mice may express learning and memory deficits with a higher concentration of long term ketamine administration, as a previous study found that adolescent rats exposed to ketamine 80 mg/kg exhibited learning and memory impairments in Morris water maze tests, rather than at the lower dose of 30 mg/kg, in a seven day administration paradigm38. Consistent with our hypothesis, the higher ketamine concentration used in this study did result in a significant spatial learning and memory impairment after six months administration instead of the three month paradigm.…”
Section: Discussionmentioning
confidence: 89%
“…did not may be due to the fact that we used adult animals (2 months old) instead of adolescent mice (1 month old); since adult mice have more well-established brain structure and defenses against neurotoxic substances than the developing or immature brain. In fact, several studies have found acute or chronic ketamine administration induced learning and memory impairment in developing or adolescent rodents more than in adulthood12131538. To exclude the effect of age in our behavioral tests results, we analyzed two control groups (Control 1 with physiological saline administration for three months and Control 2 with that for six months) and found no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 90%